The Heteromurini Absolon & Ksenemann (Collembola, Entomobryidae): a review of the genera status and diagnoses, keys for species of Alloscopus Börner and Heteromurtrella Mari Mutt and description of a new species - Cipola, Nikolas Gioia; Oliveira, Fabio Gonçalves De Lima; Morais, José Wellington De; Bellini, Bruno Cavalcante (Zootaxa, 2016)
The status of Heteromurini Absolon & Ksenemann is analyzed and a new diagnosis is proposed to the tribe. New chaetotaxic characteres were added to distinguish Dicranocentrus Schött and Pseudodicranocentrus Mari Mutt. Alloscopus Börner, Heteromurtrella Mari Mutt and Verhoeffiella Absolon, originally proposed as subgenera of Heteromurus Wankel, are reviewed and a new diagnosis and generic status are proposed. The presence of the postantennal organ becomes the main characteristic to distinguish Alloscopus (present) and Heteromurtrella (absent). Alloscopus yosiius Mari Mutt, anteriorly synonymized with Alloscopus tenuicornis Börner, is revalidated. The absence of S0 macrochaeta on head of Heteromurus is reported now as a characteristic also shared with Heteromurtrella. Heteromurtrella zairensis Tshelnokov comb. nov. is transferred from Heteromurus by the presence of macrochaetae on abdomen I. Heteromurtrella anae sp. nov. from Brazilian Amazon is described and illustrated, including detailed dorsal chaetotaxy. This is the first record of Heteromurtrella in Brazil. Heteromurus now has 17, Alloscopus 10 and Heteromurtrella 20 valid species worldwide. An identification key and diagnosis for the six genera of Heteromurini and species of Alloscopus and Heteromurtrella are provided.